Cost drivers in the pharmacological treatment of interstitial lung disease - Maqhuzu, Phillen Nozibuyiso; Kreuter, Michael; Bahmer, Thomas; Kahn, Nicolas; Claussen, Martin; Holle, Rolf; Schwarzkopf, Larissa (Respiratory research, 2021)
Introduction:  Treatments of interstitial lung diseases (ILDs) mainly focus on disease stabilization and relief of symptoms by managing inflammation or suppressing fibrosis by (in part costly) drugs. To highlight economic burden of drug treatment in different ILD-subtypes we assessed cost trends and therewith-associated drivers. - Methods:  Using data from the German, observational HILDA study we estimated adjusted mean medication costs over 36-month intervals using one- and two-part Generalized Estimating Equation (GEE) regression models with a gamma distribution and log link. Next, we determined factors associated with costs. - Results:  In Idiopathic pulmonary fibrosis (IPF) mean per capita medication costs increased from €1442 before to €11,000€ at the end of study. In non-IPF subtypes, the increase took place at much lower level. Mean per capita ILD-specific medication costs at the end of the study ranged between €487 (other ILD) and €9142 (IPF). At baseline, higher FVC %predicted values were associated with lower medication costs in IPF (−9%) and sarcoidosis (−1%). During follow up higher comorbidity burden escalated costs in progressive fibrosing ILD (PF-ILD) (+52%), sarcoidosis (+60%) and other ILDs (+24%). The effect of disease duration was not uniform, with cost savings in PF-ILD (−8%) and sarcoidosis (−6%), but increased spending in IPF (+11%). - Conclusion:  Pharmacological management of ILD, in particular of IPF imposes a substantial economic burden on the healthcare system. Strategies to reduce comorbidity burden and early treatment may reduce the impact of ILDs on the healthcare system.